2003
DOI: 10.1039/b210125d
|View full text |Cite
|
Sign up to set email alerts
|

Cloud water and throughfall deposition of mercury and trace elements in a high elevation spruce–fir forest at Mt. Mansfield, Vermont

Abstract: As part of the Lake Champlain Basin watershed study of mercury (Hg) and pollutant deposition, cloud water and cloud throughfall collections were conducted at the south summit (1204 m) of Mt. Mansfield, Vermont between August 1 and October 31, 1998, for multi-element chemical analysis. A passive Teflon string collector was deployed during non-precipitating events to sample cloud/fog water at timberline, while three sets of paired funnels collected cloud throughfall under the red spruce-balsam fir canopy. Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
(63 reference statements)
2
23
0
Order By: Relevance
“…Secondly, Hg deposition is likely to be higher in greater elevation areas. There are a few field studies [65], [66] as well as a modeling study [23]) that consider the effect of elevation on Hg deposition. Hg deposition velocities increased with increasing elevation due to increases in wind speed, although the effect may be offset by the relatively lower temperature at these sites.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, Hg deposition is likely to be higher in greater elevation areas. There are a few field studies [65], [66] as well as a modeling study [23]) that consider the effect of elevation on Hg deposition. Hg deposition velocities increased with increasing elevation due to increases in wind speed, although the effect may be offset by the relatively lower temperature at these sites.…”
Section: Resultsmentioning
confidence: 99%
“…limit must be taken into consideration. Thus, interception of dry deposition by the canopy and the subsequent enriched throughfall deposition could also contribute to enhanced deposition of atmospherically transported elements at lower altitudes (Lawson et al 2003;Avila and Rodrigo 2004). Moreover, soils under conifers may show improved retention of deposited trace elements because of greater amounts of organic acids (Lovett and Kinsman 1990).…”
Section: Distribution Of Major Metals and Trace Elements With Altitudementioning
confidence: 99%
“…Based upon soil characteristics, tree species, precipitation patterns, and expected Hg inputs, ecosystems at higher elevations are thought to receive higher Hg deposition and support greater methylation [ Lawson et al, ; Yu et al, ]. Findings of increased Hg concentrations in invertebrates, salamanders, and birds [ Blais et al, ; Townsend et al, ], along with higher concentration of other contaminants [ Reiners et al, ; Lovett and Kinsman , ; Miller et al, ; Lawson et al, ], with increases in elevation support this hypothesis. Moreover, several studies have also reported higher concentrations of soil THg in coniferous stands compared to deciduous forests [ Kolka et al, ; Graydon et al, ; Fisher and Wolfe , ].…”
Section: Introductionmentioning
confidence: 97%
“…Storage capacity of Hg within soils is enhanced by organic matter (OM) content, but the exact role of elevation remains poorly characterized [Yu et al, 2011;Townsend et al, 2014]. Based upon soil characteristics, tree species, precipitation patterns, and expected Hg inputs, ecosystems at higher elevations are thought to receive higher Hg deposition and support greater methylation [Lawson et al, 2003;Yu et al, 2014]. Findings of increased Hg concentrations in invertebrates, salamanders, and birds [Blais et al, 2006;Townsend et al, 2014], along with higher concentration of other contaminants [Reiners et al, 1975;Lovett and Kinsman, 1990;Miller et al, 1993;Lawson et al, 2003], with increases in elevation support this hypothesis.…”
mentioning
confidence: 99%